2018
DOI: 10.1177/1043659618812949
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Gaps About End-of-Life Decision Making Among Mexican American Older Adults and Their Family Caregivers: An Integrative Review

Abstract: Health professionals have a responsibility to assist older Latinos with life-limiting illnesses (LLI) and their family caregivers to make end-of-life (EOL) care decisions that are acceptable and satisfactory. Evidence shows Latinos are "low-users" of hospice services (National Hospice and Palliative Care Organization, 2018) and when they use hospice, they are less satisfied than non-Latino Whites (NLW; Agency for Healthcare Research and Quality, 2016). To investigate how much is actually known about the factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…A series of care problems and impact on family caused by bedridden and disabled family members is usually more than what the caregiver expects. Studies have shown that nearly one-third of the proxies developed negative emotions such as guild, stress, anxiety, and self-doubt after deciding the treatment for their family members, which persists for several months or even several years [31,32]. Three caregivers participated in the study mentioned that there is no dignity and meaning in living in pain like their patients.…”
Section: Discussionmentioning
confidence: 99%
“…A series of care problems and impact on family caused by bedridden and disabled family members is usually more than what the caregiver expects. Studies have shown that nearly one-third of the proxies developed negative emotions such as guild, stress, anxiety, and self-doubt after deciding the treatment for their family members, which persists for several months or even several years [31,32]. Three caregivers participated in the study mentioned that there is no dignity and meaning in living in pain like their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that participants anticipated the greatest need for more support in three items closely related to the end-of-life context: understanding the relative's illness, knowing what to expect in future, and knowing who to contact if concerned. Taking care of family members in the end-of-life stage is often full of anxiety, as the family carers may have limited understanding of the life-threatening disease and the related end-of-life decisions (Crist et al, 2019), and they may not be ready to adapt to different changes in the end-of-life caregiving trajectory (Penrod et al, 2011). Therefore, family carers may have the urge to know more about the illness and what to expect in the end-of-life care journey.…”
Section: Discussionmentioning
confidence: 99%
“…Our society, through informal local and legal national policy, tends to support treating older adults and caregivers separately and not as part of a system . The caregiving family needs to be perceived and treated as a complex system, evolving, and vulnerable to breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Our society, through informal local and legal national policy, tends to support treating older adults and caregivers separately and not as part of a system. 104 The caregiving family needs to be perceived and treated as a complex system, evolving, and vulnerable to breakdown. Foundation has also proposed a futuristic enhancement of the Patient-Centered Medical Home that is tailored to older adults and their families.…”
Section: Implications For Practice and Policymentioning
confidence: 99%